Downregulation of redox-sensitive transcription factors and neuronal ferroptosis as underlynig mechanisms of maneb-induced toxicity - Conde, Melisa Ailén (2023)
Epidemiological studies provide evidence of a strong association between the use of dithiocarbamate pesticides, such as Maneb (MB), and the risk of Parkinson’s disease. Here, we tested the hypothesis that MB increases α-synuclein expression and downregulates several redox-sensitive transcription factors, thus promoting neuronal death. For this purpose, we challenged neuronal and primary glial cultures, and mice with MB. When exposed to MB, neurons showed α-synuclein upregulation accompanied by markers of oxidative stress. This was associated with diminished glutamate-cysteine ligase catalytic subunit and heme oxygenase-1 mRNA expression and upregulation of the NRF2 repressor, BACH1. MB treatment also downregulated glutathione peroxidase 4 mRNA levels in neurons, which was coincident with increased content of reactive oxygen species, lipid peroxidation, and mitochondrial alterations. These deleterious effects were prevented by treating MB-exposed neurons with ferrostatin-1, an inhibitor of ferroptosis. In glial cell cultures, MB triggered microglial and astrocyte activation. In mice, MBinduced neurodegeneration provoked motor impairment associated with enhanced αsynuclein expression in midbrain. Our results show that MB-induced neurotoxicity downregulates NRF2 pathway and elicits neuronal death probably triggering mechanisms associated with ferroptosis.